PERILAKU RANGKAK KONDISI - Febrijanto, Rudy
Abstract: Soils failure can be caused by the lost of shear strength that caused by creep effect or continued deformation under a sustained loading. Creep deformation process is time-dependent deformations. Sustained loading takes place under constant deviator stress that lower than deviator stress at failure. Creep behavior occurs under both drained and undrained conditions. Drained creep can have both deviatoric and volumetric components and is assumed to take place under conditions of constant effective stress. Undrained creep causes changes in effective stress and is assumed to occur under conditions of constant volume and total stress. Creep tests was carried out on high plasticity soils which had high swelling potential (expansive soils). This tests were conducted on undrained conditions. The test was first conducted on 95%, 90% and 80% of maximum compaction, then creep load was applied on stress levels (or deviator load) i.e. 90%, 80% and 70% of maximum load or failure load. Research result shows that, stress levels equivalent to strain. Strain rate equivalen to stress levels. Creep failure will occur earlier on soils with the lowest safety factor (SF). Otherword, creep failure on SF = 1.1 (stress level = 90%) will occur earlier than SF = 1.25 or 1.43 (stress levels = 80% or 70%).